2021
DOI: 10.1038/s41598-021-01088-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of smoking to cg05575921 methylation in blood and saliva DNA samples from several studies

Abstract: Numerous studies have shown that cg05575921 methylation decreases in response to smoking. However, secondary to methodological issues, the magnitude and dose dependency of that response is as of yet unclear. This lack of certainty is a barrier to the use of DNA methylation clinically to assess and monitor smoking status. To better define this relationship, we conducted a joint analysis of methylation sensitive PCR digital (MSdPCR) assessments of cg05575921 methylation in whole blood and/or saliva DNA to smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…Methodological challenges are at least partially to blame for this lack of understanding. Defining the dose response of cg05575921 methylation to daily cigarette consumption and cessation greatly benefitted from the availability of two existing, readily employable, short-term biomarkers of smoking—exhaled carbon monoxide and cotinine—to help define the set point for non-smokers and to invalidate data from subjects who falsely stated that they achieved smoking cessation [ 20 ]. This was not a trivial problem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Methodological challenges are at least partially to blame for this lack of understanding. Defining the dose response of cg05575921 methylation to daily cigarette consumption and cessation greatly benefitted from the availability of two existing, readily employable, short-term biomarkers of smoking—exhaled carbon monoxide and cotinine—to help define the set point for non-smokers and to invalidate data from subjects who falsely stated that they achieved smoking cessation [ 20 ]. This was not a trivial problem.…”
Section: Discussionmentioning
confidence: 99%
“…This was not a trivial problem. While collecting the four cohorts of subjects included in a recently published meta-analysis of the dose responsiveness of cg05575921, we found that ~4% of the subjects who enrolled and stated that they were lifetime non-users of nicotine-containing products in fact had significant serum levels of cotinine [ 20 ]. This high rate of unreliable self-report is a problem for the examination of alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A droplet digital PCR (ddPCR) assay measuring methylation at cg05575921 successfully predicted smoking status in adults with varying smoking histories [151]. Also, methylation‐sensitive ddPCR assessments of the same CpG site have been shown to identify current smokers in both whole blood and saliva [152]. These examples demonstrate the effective implementation of methylation biomarkers in clinical settings to reliably assess smoking.…”
Section: Introductionmentioning
confidence: 99%